Comparative analysis of the levels of work stress, job satisfaction and work-family balance among officials of two public institutions - Chiang Vega, Margarita; Cabeza, Fernanda Cecilia; Rivera Cerda, Maria Jose (RAN - Revista Academia & Negocios, 2023)
Purpose: The objective of this study is to analyze the effect of work-family balance on job satisfaction and stress in government employees. Methodology: a causal, cross-sectional and non-experimental study was conducted, collecting data through an anonymous survey of 341 participants. Findings: work-family reconciliation had moderate levels, standing out among university staff. Low level of work stress was observed. Job satisfaction levels ranged from moderate to high. The correlations indicate that a positive perception of work-life balance is associated with better work control, and improved relationship with supervisors and collaborators. Practical implications: The findings give a valuable perspective to improve human resource management in public institutions and ensure a healthy and balanced work environment in public institutions. Originality/value: this study highlights the importance of work-life balance to improve satisfaction and reduce work stress in public institutions.